Experience in the use of a synthetic immunostimulant in the outpatient practice of a urologist - E. V. Tkachenko; A. A. Belopolsky (Лечащий Врач)
Inflammation of the prostate occurs in men of all age groups. The incidence is comparable to that of diabetes mellitus, coronary heart disease and hypertension. Chronic prostatitis significantly reduces the quality of life of patients, disrupts copulative and generative functions. According to modern data, up to 35% of men aged 20 to 40 suffer from prostate inflammation. Thus, chronic prostatitis is not only a medical but also a social problem. The results of treatment of 48 patients with a diagnosis of «chronic prostatitis», a concomitant diagnosis of «chronic recurrent chlamydia, papillomavirus infection, human papillomavirus» were analyzed. For the analysis, three groups of 48 patients were formed who received complex etiopathogenetic treatment and symptomatic therapy in accordance with Methodological recommendations number 14 of 2019, developed on the basis of the Moscow State Budgetary Healthcare Institution «City Clinical Hospital named after S. I. Spasokukotsky» of the Department of Health of the City of Moscow, Federal State Budgetary Educational Institution of Higher Education «Moscow State Medical and Dental University named after A.I. Evdokimov» of the Ministry of Health of the Russian Federation. Patients received antibacterial therapy with fluoroquinolone and tetracycline drugs in combination with an immunomodulator. As a result of treatment of a chronic inflammatory process in the prostate gland, a stable remission was achieved, and in some cases, a complete recovery of patients, confirmed by a significant decrease in the index of the scale of symptoms of chronic prostatitis and pelvic pain syndrome in men (CP-CPPS) according to the US National Institutes of Health NIH-CPSI, as well as instrumental and laboratory data. In the treatment of concomitant diseases (persistent chlamydial and papillomavirus infection), patients showed complete elimination of the pathogen and a decrease in viral load according to the enzyme immunoassay and polymerase chain reaction analysis. There were no significant side effects during treatment.